Diagnostic accuracy of intraoperative brainstem auditory evoked potential for predicting hearing loss after vestibular schwannoma surgery - Gu, Feng; Yang, Xingyu; Wang, Zilan; Tan, Xin; Xue, Tao; Chen, Zhouqing; Wang, Zhong; Chen, Gang (Frontiers in Neurology, 2022)
Objective This meta-analysis evaluated the diagnostic value of intraoperative brainstem auditory evoked potential (BAEP) for predicting post-operative hearing loss. Methods Research articles in MEDLINE, Embase, and Cochrane Library databases were searched and selected up to 20 January 2022, and data were extracted following a standard procedure. A diagnostic accuracy test meta-analysis was performed using a mixed-effect binary regression model. Results A total of 693 patients from 15 studies were extracted. The change in intraoperative BAEP showed high sensitivity (0.95) but low specificity (0.37), with an area under the curve of 0.83. Diagnostic accuracy of the loss of potentials showed high sensitivity (0.82) and specificity (0.79). The area under the curve was 0.88. No factor was found to account for the heterogeneity of the results according to the meta-regression and subgroup analyses (all P-values > 0.05). Conclusions Our results showed that the loss of BAEP has meaningful value for predicting hearing loss after vestibular schwannoma surgery. The change in BAEP is also important for its high sensitivity during hearing preservation surgery.